5-Fluorouracil encapsulated HA/PLGA composite microspheres for cancer therapy - Ooi, Chui Ping (2013)
5-Fluorouracil (5FU) was successfully entrapped within poly(lactide-co-glycolide) (PLGA) and hydroyapatite (HA) composite microspheres using the emulsification/solvent extraction technique. The effects of HA to PLGA ratio, solvent ratio as well as polymer inherent viscosity (IV) on encapsulation efficiency were investigated. The degradation and drug release rates of the microspheres were studied for 5 weeks in vitro in phosphate buffered solution of pH 7.4 at 37 °C. The drug release profile followed a biphasic pattern with a small initial burst followed by a zero-order release for up to 35 days. The initial burst release decreased with increasing HA content. The potential of HA in limiting the initial burst release makes the incorporation of HA into PLGA microspheres advantageous since it reduces the risk of drug overdose from high initial bursts. The linear sustained drug release profile over the course of 5 weeks makes these 5-FU-loaded HA/PLGA composite microparticles a promising delivery system for the controlled release of chemotherapy drugs in the treatment of cancer.